A Review on Immersive Journalism and Its Application Areas - Şahin, Z. Burcu (Atlas Journal, 2024)
The most effective and advanced examples of immersive news, which can be categorized according to the technology used in the production and consumption of news and the position of the user, constitute immersive VR news. Immersive VR news refers to a virtual reality news product that allows users to experience certain events and certain conditions from a first-person perspective. However, immersive VR news involves the presentation of a limited and framed reality, selected by its producer from the flow of time, within a specific context and for a particular audience. Similar to a fictional novel that builds its power and impact with the support of its immersiveness, it creates empathy within the framework of its reader/viewer’s personality, education, worldview, value judgments, racial, religious, and class prejudices and conveys its reality to the user within these limits. When we look at the limited examples of immersive VR journalism in the West, it is seen that its primary purpose is to draw public attention to national/international problems, environmental crises, and potential human rights violations, to create social awareness, and to mobilize a sense of empathy rather than informing the public. Immersive VR journalism offers significant potential for creating social consciousness and empathy. On the other hand, culture and arts news, documentaries, and sports news within the infotainment framework can be used as a different dimension of immersive VR journalism in today’s conditions where users’ expectations from journalism have increased with the developments in communication technologies. Immersive VR journalism, of which we see limited examples in the West, has not yet been realized at a mass level; the most common form of immersive news is 360-degree videos, of which we can see a few examples in our country. This study is based on the examination of immersive VR journalism, which has not yet become widespread in our country, within the framework of international examples. This study aims to contribute to the use of immersive VR news and journalism in national media by examining/evaluating it within the framework of potential risks and opportunities.